2021
DOI: 10.1111/ejh.13574
|View full text |Cite
|
Sign up to set email alerts
|

Clonal cytopenia of undetermined significance (CCUS) with dysplasia is enriched for MDS‐type molecular findings compared to CCUS without dysplasia

Abstract: Objectives Although morphologic dysplasia is not typically considered a feature of CCUS, we have consistently observed low‐level bone marrow (BM) dysplasia among CCUS patients. We sought to determine whether sub‐diagnostic BM dysplasia in CCUS patients is associated with other clinico‐pathologic findings of myelodysplastic syndrome (MDS). Methods We identified 49 CCUS patients, 25 with sub‐diagnostic dysplasia (CCUS‐D), and 24 having no dysplasia (CCUS‐ND). We compared the clinical, histologic, and laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
4
7
0
Order By: Relevance
“…Both CCUS with sub‐diagnostic dysplasia and CCUS without dysplasia patients were reported to display significantly fewer MFC abnormalities compared with MDS patients 6 . Our current study was consistent with this finding.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Both CCUS with sub‐diagnostic dysplasia and CCUS without dysplasia patients were reported to display significantly fewer MFC abnormalities compared with MDS patients 6 . Our current study was consistent with this finding.…”
Section: Discussionsupporting
confidence: 90%
“…One CCUS patient (#1) with mutations of SRSF2, TET2, NRAS, and Both CCUS with sub-diagnostic dysplasia and CCUS without dysplasia patients were reported to display significantly fewer MFC abnormalities compared with MDS patients. 6 Our current study was consistent with this finding. Dimopoulos et al showed that MFC had lower diagnostic sensitivity to differentiate patients with idiopathic cytopenia of undetermined significance from patients with CCUS.…”
Section: Evaluation Of Immunophenotypic Molecular Genetics and Cytoge...supporting
confidence: 92%
See 2 more Smart Citations
“…A recent report showed that the recognition of even slight dyspoietic changes (<10% of a cell lineage) in the absence of other factors known to cause myelodysplasia is closely associated with CCUS, and confers a higher risk of developing MDS, than CCUS without these findings. 24 Unspecified CCUS patients have an 80% risk of developing a myeloid malignancy within 5 years of diagnosis, 25 making the recognition of even slight dysplasia increasingly relevant even though its recognition poses a significant challenge for hematopathologists due to interobserver variability in practice as well as in this study. Patients with certain identifiable nutrient deficiencies such as copper deficiency, may also demonstrate bone marrow changes that closely mimic myelodysplasia.…”
Section: Discussionmentioning
confidence: 85%